High‐entropy alloys and compounds for electrocatalytic energy conversion applications. Issue 4 (11th November 2021) - Liu, Hang; Syama, Lenus; Zhang, Like; Lee, Carmen; Liu, Chuntai; Dai, Zhengfei; Yan, Qingyu
Abstract: High‐entropy materials, composed of five or more elements in near‐equiatomic percentage, have been attracting tremendous interests due to their advantageous properties in a variety of applications. Recently, electrocatalysis on high‐entropy alloys (HEAs) and high‐entropy compounds (HECs) has emerged as a new and promising material owing to the tailored composition and the disordered configuration of HEAs and HECs. Though extensive efforts have been devoted to investigating the catalytic nature of HEAs and HECs, the details related to the active sites and intrinsic activity of such catalysts still remain uncertain due to the complexity of the multicomponent systems. In this review, the recent progress of HEAs and HECs is systematically reviewed in terms of their synthetic strategies and electrocatalytic applications. Importantly, the computationally assisted methods (e.g., density functional theory [DFT]) are also presented to discover and design the optimum HEA‐ and HEC‐based catalysts. Subsequently, the applications of HEAs and HECs in electrocatalytic energy conversion reactions will be discussed, including hydrogen evolution reaction, oxygen evolution reaction, oxygen reduction reaction, carbon dioxide reduction reaction, nitrogen reduction reaction, methanol oxidation reaction, and ethanol oxidation reaction (EOR). Moreover, the prospects and future opportunities for this research field are cautiously discussed. A series of upcoming challenges and questions are thoroughly proposed from the experimental and theoretical aspects as well as other future applications in electrocatalysis. Abstract : In this review, the recent progress of high‐entropy alloys (HEAs) and high‐entropy compounds (HECs) is systematically reviewed in terms of their synthetic strategies and electrocatalytic applications. Subsequently, the applications of HEAs and HECs in electrocatalytic energy conversion reactions are discussed, including hydrogen evolution reaction (HER), oxygen evolution reaction (OER), oxygen reduction reaction (ORR), carbon dioxide reduction reaction (CO2 RR), nitrogen reduction reaction (NRR), methanol oxidation reaction (MOR), and ethanol oxidation reaction (EOR). Moreover, the prospects and future opportunities for this research field are cautiously discussed.